Study The effect of Annealing and Argon Laser Irradiation on the optical properties of SnO2 Thin film - N . F . Abdul-Jabbar; Z . N . Majeed; M . A . Kamil; A.M.Ali (Tikrit Journal of Pure Science, 2023)
In this research we study  the effect of Argon  Laser  Irradiation and annealing on the  some optical properties of SnO2 Thin film . These films were prepared by chemical spray pyrolysis  method. The film thickness was 1500 A°. optical properties such as (Reflection, Energy band gab, Absorption coefficient, Refractive index, and extinction coefficient) as a function of photon energy have been studied within the wavelength range (300-900) nm, using (u v-visible) Spectrophotometer, before  and after irradiation and annealing. it is found that the  optical properties were change .